INFLUENCE OF SALES AND QUALITY COSTS ON NET INCOME - Asep Mulyana (ENSAINS JOURNAL, 2020)
Abstract: This study aims to determine (1) the effect of simultaneous sales and quality costs on net income, (2) the effect of partial sales on net income, (3) the effect of cost of quality on net income at PT Ultra Jaya Milk Industry & Trading Company Tbk. By using financial statements from 2011-2017. This research uses quantitative methods and is analyzed using multiple regression analysis. The results of the study show that the results of t count sales are 4.404 while t table = 2.776 then t count> t table. While the significance value of t hitug sales variable is 0.007 <0.05. Based on these results, sales have a positive and significant effect on net income. the result of t count quality cost is 4.088 while t table = 2.776 then t count> t table. While the significance value of the t variable sales variable is 0.009 <0.05. Based on these results, quality costs have a positive and significant effect on net income. Based on this study, it can be seen that F count shows a value of 12.592, which means greater than F table, which is equal to 6.94 with a significant value of 0.019 <0.05. This shows that the regression model can be used to predict sales variables and quality costs to net income and there is a simultaneous influence between sales and quality costs on net income.Keyword: Sales, quality costs, and net profit